Nigerian Offshore Seabed: The challenges of ownership and resource control - Ogba, Sylvester Adejoh (American Journal of Humanities and Social Sciences, 2014)
<!--[if gte mso 9]> <![endif]--> In most federal states, the quest for component littoral states’ hegemony over vast mineral deposits within their territories is not necessarily novel and has been a source of political activism and litigation in many jurisdictions. The Supreme Court was confronted with the same issue for the first time in Attorney General of Federation v Attorney General Abia State & 35 ors on the ownership of the offshore seabed between the Federal Government and eight (8) states (Akwa-Ibom, Bayelsa, Cross-River, Delta, Lagos, Ogun, Ondo and Rivers) which are located on the coast (Here in after referred to as the littoral states). The court however reaffirmed the federal government sovereignty and jurisdictional control over the vast resources located in the offshore and adjacent continental shelf of the littoral states. In what follows therefore, our findings is that this judgment has deep-seated implications for municipal maritime laws, international law, seaward boundary, revenue allocation, inter-governmental relationship, national peace and security. It also raises some important issues on true federalism. The Court has given its verdict but the ghost of the argument has refused to rest and as the philosophical pendulum swings to and fro, we hope to argue that the veritable alternative hinges on the broad shoulder of political doctrine solution. The objective of this paper is to critically examine the jurisprudence behind the determination of the ownership of the Nigerian Offshore Seabed between the central government and the littoral states by the Nigerian apex court in order to consider whether the clamour for resource control is justified. In pursuits of this aim the paper employs the dialectical methodology in the sense that it examines the Nigerian legislation vis-a-vis other international jurisprudence on the issue at stake. It equally employs the philosophical tool of critical analysis in considering the various arguments forming parts of the facts in issue here. It is equally prescriptive as it recommends equity in the distribution of oil wealth through resource control as a panacea for solving the crisis. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->